Sustainability of construction materials: An overview - Gonçalves, A. (2012)
After the Brundtland Commission sustainable development is defined as “development that meets the needs of the present without compromising the ability of future generations to meet their own needs”. Initially sustainability was mainly addressed from an environmental perspective, but later the importance of social and economic issues was recognized and so they were integrated in the sustainability concept. Within the construction sector guidance documents and standards were developed establishing the basis for sustainability of materials and buildings. In this paper a review of documents on sustainability of construction works is presented along with some examples of developed applications, pointing out the difficulties on getting quality data and weighing indicators to support decision-making.